Differentiation forwarding with hotspot. (27th May 2014) - Yuan, Peiyan; Ma, Huadong
Social–based forwarding is one of the most interesting and significant topics in opportunistic networks. Whereas this scheme brings us a lot of opportunities and poses new challenges as well, due to the unique features such as the intermittently connected environment and the multi–properties pertaining to each node (e.g., the centrality and similarity). In this paper, we focus on the following questions: 1) Can we effectively evaluate node centrality and similarity in dynamic environment?; 2) Can we quickly and adaptively differentiate them only based on nodes' local observations?; 3) How does our method improve opportunistic forwarding? We propose DifferHot, a three–phase architecture for not only evaluating effectively but also adjusting adaptively the weight for centrality and similarity in social opportunistic scenarios. With the great advantage of this differentiated forwarding scheme, DifferHot helps considerably in reducing up to seven times and four times overhead in Prophet and MobySpace, respectively, while keeping delivery ratio sufficiently close to that by Epidemic.